Perbedaan rerata jumlah trombosit pada pasien demam berdarah dengue dengan manifestasi perdarahan negatif-ringan dan sedang-berat di RSUP Sanglah tahun 2015 - dinda Pradnya Paramitha Paturusi; Desak Gde Diah Dharma Santhi; Sianny Herawati (E-Jurnal Medika Udayana, 2018)
Thrombocytopenia is one of several factors causing bleeding in Dengue Hemorrhagic Fever (DHF) patients. This study was conducted to determine the characteristic of bleeding, the mean and median, and difference of mean thrombocyte count on DHF patients with negative-mild and moderate-severe bleeding manifestations at Sanglah General Hospital in 2015. This type of research is cross sectional observational analytic. Samples taken at the Sanglah General Hospital medical record. Samples obtained by consecutive sampling method and meet the inclusion and exclusion criteria. After obtaining the sample, the next procedure is to record the data that is needed in research, such as demographic data of patients, thrombocyte counts, and bleeding manifestations. Then different test were analyzed with Mann Whitney test. Of the 90 samples that meet the criteria, obtained 71,1% had negative-mild bleeding and 28.9% had moderate-severe bleeding. On the negative-mild bleeding, the most type of bleeding is negative, while in the moderate-severe bleeding is vaginal bleeding. Found also the mean and median for bleeding in negative-mild bleeding is 41.619/µl and 31.000/µl, and in moderate-severe bleeding is 26.691/µl and 22.700/µl. From Mann Whitney test p-value = 0,015 was obtained. It can be concluded that there is a significant difference between the mean thrombocyte counts in DHF patients with negative-mild bleeding and moderate-severe bleeding. Keywords: Thrombocyte, DHF, bleeding